Tell Chuēra, Kharab Sayyar und die Urbanisierung der westlichen Ğazīra : mit Beiträgen von Taos Babour und Matthias Hüls - Hempelmann, Ralph (Vorderasiatische Forschungen der Max Freiherr von Oppenheim-Stiftung ;, 2013)
Between 1999 and 2007 strata from the beginning of the third millennium B.C. exposed. They mostly date from before the "second urban revolution", when Tell Chuera also became a "city" with 80 hectares and monumental buildings, and therefore provide important information on the prerequisites and course of the urbanization process in the western Djazira. In Ralph Hempelmann's study, based on the stratigraphy and the pottery sequence, which are published in detail, a periodization is constructed, first on a local and then on a regional level, which makes it possible to pursue the question of the extent to which changes in terms of economy, society and reveal ideology. The examined material culture consists of the settlement system, the settlement structure, the installations, the floor plans of the houses, the grave forms and burial customs, the ceramic production, the small finds and the archaeozoological finds. Based on the results obtained, Hempelmann attempts to reconstruct the cultural history of the western Djazira. The study is supplemented by contributions from Taos Babour and Matthias Hüls.